The Effect of Understanding SAK-ETAP and the Quality of Human Resources on the Quality of Financial Reports in Savings and Loan Cooperatives at South Denpasar District - Ni Kadek Okta Dwi Yanti; I G A Astri Pramitari; I G A Oka Sudiadnyani (Journal of Applied Sciences in Accounting, Finance, and Tax, 2022)
The existence of cooperatives as a support for the people's economy to support Indonesia's economic growth. Financial reports are one of the important factors as a report on the accountability of cooperative management and the condition of cooperatives to members and owners of cooperatives in the main forum that must be held by every cooperative, namely RAT. In preparing quality financial reports, it is necessary to have an understanding of SAK-ETAP, and quality human resources. This study aims to determine the effect of understanding SAK-ETAP, and the quality of human resources partially and simultaneously on the quality of financial reports. The location of this research is the Savings and Loan Cooperative in South Denpasar District. The population in this study were employees of the Savings and Loans Cooperative in South Denpasar District and the sample in this study was 70. The data analysis techniques used in this study were Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, F Test, T test and Coefficient of Determination Test. From the results of the study, it can be seen that: (1) understanding of SAK-ETAP has a significant positive effect on the quality of financial reports (2) the quality of human resources has a significant positive effect on the quality of financial reports. 3) Simultaneously understanding of SAK-ETAP and the quality of human resources have a significant effect. on the quality of financial reports. The magnitude of the influence of understanding SAK-ETAP and the quality of human resources on the quality of financial reports is 57%. Suggestions that can be given by researchers are Savings and Loans Cooperatives in South Denpasar District are expected to routinely provide training and guide employees